1993
DOI: 10.1080/03075079312331382281
|View full text |Cite
|
Sign up to set email alerts
|

Staff and peer-group assessment of oral communication skills

Abstract: During student presentations the oral communication skills of final year BSc pharmacology students were assessed by their peer group and by a group of academic staff. That there was agreement between staff and peers about the absolute and relative quality achieved in the presentations is indicated by the significant positive correlation between the two sets of marks awarded to individuals and the agreement about which presenters constituted the top and bottom quartiles of the mark list. The standard of present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 0 publications
8
39
1
3
Order By: Relevance
“…The findings of this study are in line with the findings of other studies which found a positive effect for peerevaluation on the improvement of students' writing performance (Hughes & Large, 1993;freeman, 1995;Dyer, 1996;Brown, 2001). The findings are in also in line with the study of Patri (2002) which found that when assessment criteria are set, peer-assessment can enable students to judge the writing of their peers in manner comparable to their teachers.…”
Section: Discussionsupporting
confidence: 82%
“…The findings of this study are in line with the findings of other studies which found a positive effect for peerevaluation on the improvement of students' writing performance (Hughes & Large, 1993;freeman, 1995;Dyer, 1996;Brown, 2001). The findings are in also in line with the study of Patri (2002) which found that when assessment criteria are set, peer-assessment can enable students to judge the writing of their peers in manner comparable to their teachers.…”
Section: Discussionsupporting
confidence: 82%
“…Shared learning gives students an opportunity to engage in discussion, take responsibility for their own learning, and thus become critical thinkers (Totten, Sills, Digby & Russ, 1991). Group work can be used to encourage deeper learning and promote students' autonomy by transferring some of the responsibility for teaching and learning to them (Hughes & Large, 1993;Somervell, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the variability of both groups was equivalent. Hughes and Large (1993) also found this to be the case for PA of oral communications, but as noted by Topping (1998), there are few studies looking at the relative abilities of assessors and assessee. In this study, the marks for PA for all students were signifi cantly higher than for CAA practicals, although in absolute terms this was not of any consequence for this unit.…”
Section: Discussionmentioning
confidence: 99%